Incivilidades nas redes sociais online sob as lentes da regionalidade: vulgaridades, depreciações, ameaças e mentiras - Cândido, Leandro Borges (2019)
Social network sites revolutionized the way people communicate, Interact, receive and disseminate information. With the raise of its popularity, particularly Facebook, the social network with the largest number of users, more individuals begin to have access, participate and engage in discussions about social and political issues. Despite fostering interaction between people, without the need of physical spaces, social network sites are often used e exploited to spread degrading, abusive and harmful content about individuals or groups, usually that content is connected to social and moral patterns from the dominant groups. Within this context emerge the online incivilities, that can be understood as the disrespect of the collective traditions of democracy, denying people their personal freedom and stereotyping social groups. Beyond that, are still understood as acting rudely, discourteous, without consideration for the other, breaking norms of respect, by means of rude critiques, cursing, offensive affirmations, hate speech, harassment, violence, threats and humiliation. Inside the context of the presidential elections of 2018, where there has been a greater polarization e aggressiveness, we established as the general purpose of this study to comprehend the specificities of uncivil behavior whereas a phenomenon unleashed in social network sites, in Facebook pages that expressed support to right and extreme right partisans. We performed a qualitative research in fifteen Facebook pages from the state of Minas Gerais, using Netvizz to collect the data. To operationalize the research, we were guided by two needs: 1) to apprehend the specificities of online incivility and 2) discusses its incidence. We analyzed 1.909 posts and 102.116 comments, that after being scraped bear a research corpus of 3.019 comments. The data were submitted for textual analysis in IRAMUTEQ and ATLAS.ti software and also analyzed under the perspective thematic content analysis, generating four categories of uncivil discourse. The results showed that between the members of these Facebook pages there are a dissemination and validation of the uncivil discourse, being the most common the outrage, curses, stereotypes, aspersion, vulgarities, lies, depreciation, gender and racial discrimination, offenses and foul language. Besides that, the homophily between members allows a major engagement, encouragement and tolerance towards incivility.